A Taxonomy for the Activist Environment: On Atmosphere and the Ad Hoc. Issue 1 (2nd January 2019) - Goodman, David
Abstract : In this essay, I identify novel strategies for the activist mode of architectural thought and production, strategies that suggest a shift from architectural activism as the authorless production of events and artifacts to the production of authored environments and atmospheres. I develop this taxonomy in part by drawing on the disagreement between American art critics Clement Greenberg and Harold Rosenberg over the status and objectives of what would come to be called action painting. The goal of this taxonomic approach is to propose strategies through which a socially engaged architecture might generate authored physical atmospheres, transcending the domain of authorless processes, actions, and ad hoc artifacts increasingly common today.